THE RELATIONSHIP BETWEEN EMPATHY AND PROSOCIAL BEHAVIOR OF NON-DISABLED STUDENTS TOWARDS STUDENTS WITH DISABILITIES SPECIAL EDUCATION STUDY PROGRAM FKIP SEBELAS MARET UNIVERSITY - Wahyu Abdi Prastyo; Dewi Sri Rejeki; Mahardika Supratiwi (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
This study aims to determine the relationship between empathy and prosocial behavior of non-disabled students towards students with disabilities. Special Education Study Program (PKh) FKIP Sebelas Maret University. This research is a quantitative research of the correlational type This research was conducted at Sebelas Maret University, Special Education Study Program, involving non-disabled students of the 2020, 2021, 2022, and 2023 batches. The data collection method uses an online questionnaire where respondents need to fill out the available forms. Data analysis uses inferential statistics. The results of the study showed a considerable strong correlation between empathy and prosocial behavior with a negative correlation in non-disabled students in the Special Education Study Program (PKh) FKIP UNS. It is hoped that this research will be a reminder for Special Education Study Program students to pay attention to the use of empathy as necessary in daily life.